Revealing the hidden impact of SGLT2 inhibitors on uric acid levels: a retrospective multicenter cohort study - Habeeb, Ehsan A.; Ghaith, Abdullah M.; Alshehri, Abdulmajeed M.; Aquil, Ghalia; Afana, Arwa H.; Alqarafi, Ali H.; Alahmed, Abdullah A.; Alkhezi, Omar S. (Frontiers in Endocrinology, 2025)
IntroductionHyperuricemia, characterized by elevated serum uric acid (UA) levels, is associated with cardiovascular–kidney–metabolic syndrome and remains challenging to manage due to medication side effects and adherence issues. SGLT2 inhibitors (SGLT2i), primarily prescribed for diabetes (DM), heart failure (HF), and chronic kidney disease (CKD), have demonstrated potential UA-lowering effects, though their precise impact is not well established.MethodsThis multicenter retrospective cohort study used a pre-and-post analysis to evaluate the effect of SGLT2i on UA levels. Data were collected from four major healthcare centers in Saudi Arabia. The study included adult patients who initiated SGLT2i therapy between January 2022 and January 2024, excluding those with active gout flares, a history of cancer, or recent changes in UA-lowering therapy. The primary outcome was the percentage change in serum UA levels post- i initiation, with secondary outcomes including subgroup analyses, metabolic effects, univariate and multivariate modeling, and longitudinal trend evaluations.ResultsAmong 2,400 patients screened, 454 were included in the final analysis. SGLT2i significantly reduced UA levels by 4.5% (p=0.006), with the most pronounced reduction in patients with baseline elevated UA (10%, p=0.001) and those with HF (9%, p=0.001). Univariate analysis identified DM & HF, DM & CKD, and DM, HF & CKD as predictors of response, but multivariate analysis confirmed only DM & HF as an independent predictor (OR = 2.2, 95% CI: 1.2–4.04).ConclusionThese findings suggest that SGLT2i may serve as an adjunct therapy for hyperuricemia, especially in patients with DM & HF, highlighting the need for further research on long-term benefits.